Imitate me!—preliminary tests on an upper members gestures recognition system - Silva, Vinicius Corrêa Alves (2017)
This work describes the design, implementation, and preliminary tests of a system that uses a humanoid robot to mimic non-standard upper members gestures of a human body. The final goal is to use the robot as a mediator in motor imitation activities with children with special needs, either cognitive or motor impairments. A Kinect sensor and the humanoid robot ZECA (a Zeno R-50 robot from Hanson RoboKind) are used to identify and mimic upper members gestures. The system allows direct control of the humanoid robot by the user. The proposed system was tested in laboratory environment with adults with typical development. Furthermore, the system was tested with three children between 4 and 12 years old with motor and cognitive difficulties in a clinical-like environment. The main goal of these preliminary tests was to detect the constraints of the system.